Upaya Orang Tua dalam Mendorong Tumbuh Kembang Anak Penderita Disleksia - Halen Dwistia; Rahma Wulandari; Nia Asmara; M. Yusron Zakya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This type of research is qualitative research with a descriptive approach and library research. This research aims to determine parents' efforts to encourage the growth and development of children with dyslexia. The subjects of this research were children suffering from dyslexia with the initials A. Data collection techniques used observation methods in their research, and various sources of reviews of other research articles. The results of this research are that the first step that parents can make is to introduce the letters of the alphabet in an interesting way, such as inviting children to watch educational videos about the alphabet, parents start teaching children to put words together slowly. So that children understand better, parents can start teaching them how to spell words clearly. And parents can also provide emotional support to children so that children are more confident and motivated in reading